Designing an interprofessional dementia specialty clinic: Conceptualization and evaluation of a patient-centered model. Issue 2 (4th March 2023) - Aguirre, Alyssa; Hilsabeck, Robin C.; O'Mahar, Kerry; Carberry, Kathleen E.; Ayers, Gayle; Bertelson, John; Rousseau, Justin F.; Paydarfar, David
ABSTRACT: The need for blueprints to design specialty care interprofessional collaboration (IPC) models is urgent, given the expanding aging population and current challenges in dementia diagnosis and treatment. We describe key steps creating an interprofessional outpatient dementia specialty clinic, efforts to sustain the model, and evaluation of interprofessional effectiveness and clinician satisfaction. The conception for the Comprehensive Memory Center was informed by qualitative research methodologies including focus groups, interviews, and literature reviews. Quantitative evaluation included satisfaction surveys and team effectiveness measures. The IPC model diverges from typical dementia practices through its interprofessional team, visit structure, approach to decision-making, in-house services, and community collaborations. Team retreats and workshops helped build clinician knowledge of interprofessional values and practices to sustain the IPC model. In the first 3.5 years, we served nearly 750 patients and their caregivers. Team evaluation results revealed that increased access to consultation and sharing the workload and emotional burden were beneficial. The majority of team members preferred the IPC model to traditional models of clinical care.